The Effect Of Compensation, Motivation And Work Ethic On The Performance Of Employees Of Ernaldi Bahar Hospital, South Sumatra Province - Tien Yustini; Luis Marnisah; Yusnila Rochmah (Syntax Corporation, 2022)
The purpose of this study is specifically to obtain the results of the analysis of the effect of compensation, motivation and work ethic on employee performance, either partially or simultaneously. The research method uses an analytical survey, data collection is done by interview using a questionnaire. This research is associative research, where in this study there are variables that are related and can influence other variables. The samples in this study are the total population, namely all administrative employees of Ernaldi Bahar Hospital with the status of Civil Servants totaling 113 people. Data processing using SPSS. Testing the data using the t-test, shows that the Sig value for each variable is Compensation (X1) = 0.000; Motivation variable (X2) = 0.014; and work ethic variable (X3) = 0.001 smaller than 0.05. The results of this research indicate that compensation, motivation, and work ethic (independent variable) partially affect the employee performance variable (dependent variable). Based on testing the data using the F test, the value of Sig (0.000) <0.05 was obtained. Thus it is concluded that compensation and motivation as well as work ethic have a simultaneous effect on performance. The common thread of research is that compensation and motivation as well as work ethic have a positive and significant effect on the performance of Ernaldi Bahar Hospital employees, either partially or simultaneously. The strategy to improve the performance of the Ernaldi Bahar Hospital employees can be done by first formulating the compensation given to employees by considering the workload, then building work motivation to help each other in completing the work and finally increasing the employee's work ethic by providing adequate facilities in carrying out the work.